Determining the origins of carbon-13 enrichments in biomineralized fissure calcrete deposits from the western northwest territories, Canada: Comparing acetogenic and methanogenic bacterial processes - Marschner, Mark (University of Ottawa (Canada), 2006)
The occurrence of secondary carbonate deposit within limestone fissures, called "endostromatolites", is evidence of biomineralization occurring in Canada's permafrost regions. Clustered growth columns propagating orthogonally to the fissure surface grew under saturated conditions during a period of climate amelioration after the end of the last major period of glaciation in North America (∼ 13 000 years b.p.). The enriched delta 13C signal along endostromatolite growth columns (compared to the host rock) was previously interpreted as the result of methanogenesis. A conceptual model of the original growth environment links bacterial communities in soil horizons overlying the limestone outcrops with the microorganisms living within the rock mass. A field investigation of surface waters within the thawed active layer above permafrost in a periglacial limestone terrain did not show any 13C-enrichment trends in DIC (dissolved inorganic carbon). Microsampling of individual growth columns from endostromatolite hand specimens yielded delta 13C values enriched compared to the host rock but no real trends along the growth column that could be used as clear evidence of a Rayleigh-type distillation process (i.e. the isotopic enrichment of a residual substrate). A series of laboratory closed-system incubation experiments using bacterial communities cultured from field materials was performed. Acetogenesis, rather than methanogenesis, was the predominant process at low temperatures and/or when DIC was provided as a substrate. The development of new methodologies, including compound-specific isotopic analyses of DOC components in complex matrices, provided enough results for a carbon mass balance to be calculated on the systems. A very distinct Rayleigh-type 13C-enrichment trend was observed for methanol as a substrate, but enrichment of DIC was ubiquitously short-lived due to negative feedback signals from production of 12CO2. However, DIC enrichment occurred during production of acetate, thus pointing to the origin of enriched delta13C signals in endostromatolites as being from acetogenic processes. Keywords. endostromatolite; acetogenesis; methanogenesis; permafrost; 13C; 18O; DIC.
Keywords: Geology.